A Strategic Framework for a Smart Campus: American University of Sharjah Case Study - AbuAlnaaj, Karam Hani (2019)
A Master of Science thesis in Engineering Systems Management by Karam Hani AbuAlnaaj entitled, “A Strategic Framework for a Smart Campus: American University of Sharjah Case Study”, submitted in November 2019. Thesis advisor is Dr. Vian Ahmed. Soft copy is available (Thesis, Approval Signatures, Completion Certificate, and AUS Archives Consent Form).